(untitled) (Jurnal Adabiya, 2020)
This article presents an outlook of pidgins and creoles starting from the background of the arise of the using of pidgins and creoles in the world. To have a clear understanding of what pidgins and creoles are the definition of both terms are explained briefly here. This article also discusses some distinctions or distinctive features of pidgins and creoles and the community using pidgins and creoles in the world. At the end of the discussion, this article describes some brief discussions related to some reasons stating that pidgins and creoles are born as languages.